Distribution mapping of building classification and air pollution exposure in the urban city areas by using GIS-based application: A pilot study - Norsaffarina, Aziz; Paramjothy, Navin Kumaran; Mohammad Adam, Adman; Syarifuddin, Misbari; Lee, Lim Fang (Penerbit UMP, 2024)
This study explores the association between the locations of building classification and air pollution, focusing on the particulate matter concentrations (PM2.5) in Kuantan city. It emphasizes the influence of building classification on selected locations in the urban city area and PM2.5-related health hazards. PM2.5 were measured at selected areas that have been classified as high-rise and low-rise building areas in the Kuantan city centre. The selected study locations were also mapped with the GIS mobile application to have a better understanding through visualization. Locations that has been identified as the high-rise buildings area had a greater PM2.5 concentrations than the low-rise buildings area due to constrained airflow. To minimize the PM2.5 pollution, it is recommended to consider building design, air pollutant dispersion strategies, and introducing green spaces in the urban city area. A further study is needed to address these mitigation factors to improve the ambient air quality in the urban city area.